Perancangan Dan Implementasi Aplikasi Elearning Berbasis Web Dan Android - Miftahul Huda (Politeknik Sawunggalih Aji, 2022)
One of the applications in the internet-based and website-based and android-based learning process is elearning. Problems that often arise in the learning process require an elearning media which is expected to help lecturers and students in providing information in the form of materials, assignments, discussions and exams that can be done anywhere quickly and efficiently. Therefore, it is necessary to plan and implement elearning in the learning process. The method in this research is the research and development method (Research and Development). The method is used to obtain information about user needs while development activities are carried out to produce learning tools. The result of this study is to produce web-based and android-based elearning applications. The elearning application was created using the Moodle LMS based on the analysis of the ongoing system as well as from the analysis of the system design. The elearning application is also tested with several browsers and the elearning application runs well. Elearning applications can be run using a Desktop PC or Android